Environmental & architectural phenomenology. Vol. 10, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1999)
Vol. 10, No. 3, Fall 1999 (includes “items of interest,” "citations received,” book reviews of Yi-Fu's Cosmos and Heath and Wendell Berry's Another Turn of the Crank, essays by David Seamon & Tom Jay, and poems by Miles Richardson & Judyth Hill).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals